Cortical features of distinct developmental trajectories in patients with delusional infestation - Hirjak, Dusan; Kubera, Katharina Maria; Wolf, Robert Christian (Progress in neuro-psychopharmacology & biological psychiatry, 2017)
Background: Although there is strong neuroimaging evidence that cortical alterations are a core feature of schizophrenia spectrum disorders, it still remains unclear to what extent such abnormalities occur in monothematic delusional disorders. In individuals with delusional infestation (DI), the delusional belief to be infested with pathogens, previous structural MRI studies have shown prefrontal, temporal, parietal, insular, thalamic and striatal gray matter volume changes. Differential contributions of cortical features of evolutionary and genetic origin (such as cortical thickness, area and folding) which may distinctly contribute to DI pathophysiology are unclear at present. Methods: In this study, 18 patients with DI and 20 healthy controls (HC) underwent MRI scanning at 1.0T. Using surface-based analyses we calculated cortical thickness, surface area and local gyrification index (LGI). Whole-brain differences between patients and controls were investigated. Results: Surface analyses revealed frontoparietal patterns exhibiting altered cortical thickness, surface area and LGI in DI patients compared to controls. Higher cortical thickness was found in the right medial orbitofrontal cortex (p<0.05, cluster-wise probability [CWP] corrected). Smaller surface area in patients was found in the left inferior temporal gyrus, the precuneus, the pars orbitalis of the right frontal gyrus, and the lingual gyrus (p<0.05, CWP corr.). Lower LGI was found in the left postcentral, bilateral precentral, right middle temporal, inferior parietal, and superior parietal gyri (p<0.01, CWP corr.). Conclusion: This study lends further support to the hypothesis that cortical features of distinct evolutionary and genetic origin differently contribute to the pathogenesis of delusional disorders. Regions in which atrophy was observed are part of neural circuits associated with perception, visuospatial control and self-awareness. The data are in line with the notion of a content-specific neural signature of DI.